Caboclos, indígenas e colonos: a mediação da comissão de terras e colonização de Passo Fundo e Palmeira no processo de formação da pequena propriedade no norte rio-grandense (1889-1928) - Schmitz, Kalinka de Oliveira (2019)
This dissertation aims to analyze the process of (re)organization of land ownership in the North of the Rio Grande do Sul during the First Republic and the subjects involved. Starting from the fact that this region was inhabited centuries ago by native people and from the nineteenth century by caboclos, the arrival of the colonial population, beginning in 1890, it unleashed a rearrangement of the scenery of the property; in addition, government actions to advance of regularization land ownership impacted in different ways the groups involved. So, there was looked systematically the installation of the native groups in awnings, restricting its area of occupation, also altering their customs by forcing a sedentarization; the caboclos, who were initially very marginalized, passed with Torres Gonçalves – to be included in colonization projects, to end the expulsion of them from areas occupied for a long time; and the settlers, who migrated to the Rio Grande do Norte region in search of new fertile lands, eventually came into contact not always friendly to the first two groups. Therefore, it is these changes that will be analyzed here, seeking to understand the first actions in the privatization movement of land ownership, and how this affected each group. In this context, our study aims to analyze the process of access and ownership of land in the North of Rio Grande do Sul in the First Republic (1889-1930), with the objective to check the list of discussion and the action of the state government and the public agencies responsible for land and colonization. The comparative analysis is delimited to the work of the Land and Colonization Commission of Passo Fundo and the Land and Colonization Commission of Palmeira, as well as their areas of scope, with regard to the regularization of land ownership, and the implementation of policies aimed at the establishment of native peoples, caboclos and settlers.